A comparative study of learning organisation practices of Indian businesses. (2017) - Bhattacharya, Sonali; Neelam, Netra; Behl, Abhishek; Acharya, Sabyasachi
Purpose: In this study we compared the learning organisation practices of Indian Businesses across sectors. Methodology: The study is based on a sample of 406 managers of banking, information technology and information technology enabled services (IT/ITES), manufacturing, hotel & hospitality and hospital and healthcare sectors. Learning organisations have been assessed through lens of holistic framework, strategic thrust, shared vision, empowerment, information flow, emotional maturity or internality, learning and synergy which are considered as managerial levers of dynamic capability. Findings: It was found that profiles of Indian businesses are perceived to have low to medium level performance in dimensions of learning organisation (LO) practices across sectors. They are found to be low in internality or emotional maturity but high in strategic thrust. Among the business sectors, hotel & hospitality services & manufacturing industries have significantly higher LO scores Significance of dimensions of LO differ across sectors as captured through sector-wise exploratory factorial analysis (EFA).